دور الصوائت في تحديد المعنى لدى القدامى والمحدثين / The Role of the Vowels in Determining The Meaning Among The Traditional and Modern Scholars - Rahmani, Abdul Razak (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2017)
ملخص البحث: عرف اللغويون العرب الصوائت منذ زمن بعيد؛ حيث كانت تستخدم دون رمز يثبت وجودها، وكان القارئ يدركها من خلال فهمه للنص أو السياق، وتؤكد معرفتهم لهذه الأصوات، منذ أن كانت اللغة العربية في صورتها المنطوقة قبل الكتابة. يقوم بناء المفردة في اللغة العربية على الصوامت والصوائت، وتحمل الصوامت المعنى الأساسي للمفردة؛ أما الصوائت فتقوم بدور بنّاء لتغيير المعنى وتخصيصه على صيغ معينة. ولما كانت الصوامت والصوائت تؤلفان جزئي البناء اللفظي للكلمة، ظهرت الحاجة إلى دراستهما في جانب المعنى. اتبع البحث المنهج الوصفي التحليلي، وهدف إلى بيان أثر الصوائت في بيان المعنى لدى القدامى والمحدثين. توصلت الدراسة إلى إنّ مؤلفاتِ علماء العربيّة تُعتبر مصدراً أصيلاً يزخر بالمباحث والدراسات الصوتية العميقة، وأن هناك حاجة إلى إعادة صياغة تعريفات العلماء المتقدمين للأصوات الصائتة، في ضوء ما أثبته الدّرس الصّوتي الحديث، وأن ابن جني هو أول من استعمل مصطلحاً فنياً للدلالة على الأصوات، وأن علماء الأصوات القدامى قد استطاعوا تحديد مصدر تلك النغمة الخاصة التي تنبعثُ مع الأصوات دون استخدام وسائل وأجهزة حديثة، وأنّ الانحراف عن الصوت المعين للحركة في المكان المحدد له، يسبب وقوع خلل مؤكد في بناء المفردة، ويتبع ذلك إزالة معناها الكلمات المفتاحية: الصوائت- المعنى- الأصوات- القدامى- حروف المد. Abstract: Arab traditional scholars had identified the vowels since a very long time ago without using any symbol to indicate their existence as the readers were able to identify them from the context of text and proved their knowledge about them in their expressed forms before the Arabic language had its written letters. Word construction is based on the vocals and vowels; the former carries the basic meaning of the word while the latter constructively change the meaning and specify it to specific forms. Since both make partial construction of the word, there arises the need to study them from the aspect of meaning. The study is descriptive and analytical aiming at explaining the effects of vowels on meaning among the traditional and modern scholars. It reveals that the compilations of the Arabic scholars are regarded as original reference rich with in depth phonetical discussions and studies; there is a need to review the traditional scholars’ definitions for the vowels in the context of modern phonetic studies; Ibnu Jinni was the first to employ technical terms to refer to phonetical sounds; traditional scholars, without even using the instruments used my modern scholars, managed to trace the source of that special intonation that accompany the voice; the deviation from certain sound for vowel pronunciation in its respective place will result in certain flaw in word construction which would lead to diminishing its meaning. Keywords: Vowels, Meaning, Voices, Traditional scholars, Long vowels Abstrak: Pengkaji Bahasa Arab tradisional telah mengenalpasti huruf-huruh vowel semenjak dahulu lagi tanpa menggunakan apa-apa simbol untuk menunjukkannya memandangkan para pembaca dapat mengenalnya daripada konteks dan teks walaupun ketika itu Bahasa Arab masih belum lagi mempunyai sistem penulisan yang lengkap. Pembentukan perkataan adalah berdasarkan huruf-huruf vokal dan vowel. Maksud asas sesuatu perkataan dibawa oleh huruf vokal manakala vowel mengubahnya mengikut struktur tertentu berdasarkan makna yang diinginkan. Oleh kerana kedua-duanya terlibat dalam pembentukan makna maka adalah penting untuk mengkaji peranannya dari segi makna. Kajian ini adalah deskriptif dan analitikal. Objektifnya ialah untuk mengkaji menerangkan kesan-ksan vowel ke atas makna dalam kalangan pengkaji bahasa tradisional dan moden. Antara dapatan kajian yang penting ialah: karangan pengkaji tradisional bahasa Arab adalah amat asli dan kaya dengan kupasan mendalam berkenaan aspek fonetik; terdapat keperluan untuk melihat semula definisi pengkaji tradisional berkenaan huruf vowel dalam konteks pengkajian fonetik moden; Ibnu Jinni adalah di antara pelopor yang memberikan pendefinisian teknikal tentang vowel; pengkaji tradisional, tanpa menggunakan peralatan moden, mampu untuk mengesan punca intonasi yang bersama dengan suara; perubahan bunyi daripada sesetengah vowel pada tempat penghasilannya akan membawa kepada kelemahan dalam pembentukan huruf yang akan mebawa kepada kekurangan makna. Kata kunci: Vowel, Makna, Suara, Pengkaji Tradisional, Vowel panjang.